When a constant is the numerator

For example,

$\displaystyle

z = \frac{x}{y+1}

$

Can I rewrite it as $\displaystyle z = x(\frac{1}{y+1})$

So that $\displaystyle \frac {\partial z}{\partial y}= 0 + x[- \frac {1}{(y+1)^2}]$

Printable View

- Mar 14th 2009, 09:28 PMcammywhiteWhen a constant is on top of a function
When a constant is the numerator

For example,

$\displaystyle

z = \frac{x}{y+1}

$

Can I rewrite it as $\displaystyle z = x(\frac{1}{y+1})$

So that $\displaystyle \frac {\partial z}{\partial y}= 0 + x[- \frac {1}{(y+1)^2}]$ - Mar 14th 2009, 09:34 PMoswaldo
Yes. But you don't need to:

$\displaystyle

\frac {\partial z}{\partial y}= \frac {0(y+1)-1(x)}{(y+1)^2}

$

gives the same answer.

-O